(untitled) (International Journal of Nursing Education, 2021)
Natural Disasters can happen at any place irrespective of the developed, developing or the least developedstatus of a country. It can cause massive destruction to the lives and livelihoods of large population andhence, to the national economies. It is experienced that the least developed and developing countries areimpacted more severely by large scale natural disasters especially the flood. A number of studies haveshown a range of symptoms resulting from exposure to natural disasters such as flooding. Among theseconsequences, individuals may experience symptoms of post-traumatic stress disorder (PTSD), depressionand anxiety. The aim of this article was to examine the psychological impact of flooding.